Sistemas tampão: uma estrutura didática teórico-prática - Rossi-Rodrigues,Bianca Caroline (2009)
Courses with practical and theoretical classes are potentially didactic structures for the development of motor and complex cognitive skills when operated in an integrated manner. When worked aligned, theory and practice enable a clearer view of the issue, opening scope for introducing concepts from other disciplines and for the development of lab skills. This paper presents a methodology for biochemistry labwork that promotes the teaching of the buffering systems contents together with to the development of scientific research practice concepts in an interdisciplinary perspective that integrates theory and practice.